PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG, DAN PERPUTARAN PERSEDIAAN MODAL TERHADAP PROFITABILITAS PERUSAHAAN SEKTOR AGRICULTURE DI BURSA EFEK INDONESIA PERIODE 2018-2020 - NAOMI THERESIA IRMAWAN; LENITA WATY (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2022)
This study aims to determine the effect of cash turnover,  receivables  turnover, inventory turnover, and  working  capital  turnover  on  the  profitability  of  agriculture  sector  companies  listed  on  the  Indonesia   Stock  Exchange  for the 2018-2020 period.  The  independent  variables  in  this  study  are  cash turnover,  accounts  receivable  turnover,  and  working   capital   inventory turnover. And the dependent variable in this study is profitability. The population  in  this  study  are  agriculture  sector  companies  listed  on the Indonesia  Stock  Exchange.  The  sampling  technique  used  in  this  study  used a  purpose  sampling  technique.  According  to  the  criteria  that  have  been set in the sampling, there  are  8  companies  that  fit  the  criteria.  The  type  of  data used is secondary data taken  by  the  documentation  method  by  accessing  the www.idx.co.id site. As well as the sites of each company. The analysis  technique used is multiple linear regression analysis technique. The results showed that: (1) There is a positive influence between cash turnover on company profitability.  (2)  There  is  no  influence  between  receivables  turnover  on  company  profitability.  (3)  There  is  a  positive  influence between inventory turnover on company profitability. (4) There is a negative influence between working capital turnover on company profitability.